Performance Audit on Tribal Sub Plan Schemes in Health Domain in Madhya Pradesh - CAG of India (CAG of India)
Some of the main audit findings were: 1. Annual Action Plan for NPCDCS and NPHCE programmes and database on physical, financial and epidemiological profile was not prepared at State and district levels. 2. Information, Education and Communication for general awareness of the non-communicable diseases were not carried out at State and district levels. 3. There were shortages of geriatric wards, clinics, essential drugs, machinery and equipment in NCD clinics mainly due to under-utilisation of funds. 4. Due to non-deployment of medical and para-medical staff, health care services could not be provided efficiently under the programmes.